Voices from the dust: new insights into ancient America - Calderwood, David G. (Historical Publications, 2005)
"A comparative evaluation of early Spanish and Portuguese chronicles, sixteenth and seventeenth century New World conquistadores and colonizers, the Book of Mormon, and Latin American archaeology and art history"--Provided by publisher